Immunological Mechanisms Underlying Chronic Pelvic Pain and Prostate Inflammation in Chronic Pelvic Pain Syndrome - Breser, María L.; Salazar, Florencia C.; Rivero, Viginia E.; Motrich, Rubén D. (Frontiers in Immunology, 2017)
Chronic prostatitis/chronic pelvic pain syndrome (CP/CPPS) is the most common urologic morbidity in men younger than 50 years and is characterized by a diverse range of pain and inflammatory symptoms, both in type and severity, that involve the region of the pelvis, perineum, scrotum, rectum, testes, penis, and lower back. In most patients, pain is accompanied by inflammation in the absence of an invading infectious agent. Since CP/CPPS etiology is still not well established, available therapies for patients are far from satisfactory for either physicians or patients. During the past two decades, chronic inflammation has been deeply explored as the cause of CP/CPPS. In this review article, we summarize the current knowledge regarding immunological mechanisms underlying chronic pelvic pain and prostate inflammation in CP/CPPS. Cumulative evidence obtained from both human disease and animal models indicate that several factors may trigger chronic inflammation in the form of autoimmunity against prostate, fostering chronic prostate recruitment of Th1 cells and different other leukocytes, including mast cells, which might be the main actors in the consequent development of chronic pelvic pain. Thus, the local inflammatory milieu and the secretion of inflammatory mediators may induce neural sensitization leading to chronic pelvic pain development. Although scientific advances are encouraging, additional studies are urgently needed to establish the relationship between prostatitis development, mast cell recruitment to the prostate, and the precise mechanisms by which they would induce pelvic pain.